UPAYA MENINGKATKAN KETERAMPILAN MOTORIK KASAR ANAK USIA DINI MELALUI PERMAINAN DENGKLEK KELAS B DI TK J – A RUMMI JATISARI JENGGAWAH JEMBER - Aldilla Ventri Kasony; Wijaya Adi Putra; Muhammad Agus Sugiarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the gross motor skills of early childhood children through the traditional game activity Dengklek. The researcher used classroom action research (PTK) with the Kemmis and McTaggart model, which consists of four stages: planning, implementation, observation, and evaluation. The research was conducted at TK J – A RUMMI Jatisari, Jenggawah, Jember, involving 28 students in group B.Data collection techniques used were observation results and documentation. The results of the study showed that in the pre-cycle, 8 children (28.5%) achieved the expected level of development. In cycle 1, 13 students (46.4%) reached the target, and in cycle 2, there was an increase to 23 students (82.1%).It can thus be concluded that the Dengklek traditional game activity can improve the gross motor skills of early childhood children, as evidenced by the results of the research conducted at TK J – A RUMMI Jatisari, Jenggawah, Jember.